远距离输送链传动载荷分析及其磨损伸长研究 - 赵俊天; 王顺增; 王振兴 (Jixie chuandong)
Wear is the major factor of chain damage.The static and dynamic load calculation of the long-distance transmission roller chain is carried out.Through the analysis of theory formula,a conclusion which has a larger impact the wear of chain pitch on the excitation force in the transmission vibration in the process of chain transmission is obtained.As to this,the theoretical calculation formula of each chain load and the formulaic relationship between load and elongation of chain pitch are obtained based on the point-by-point static load model and chains/sprockets meshing model.For the analysis and verification of the theoretical results using RecurDyn software for numerical simulation,the distribution curve of the load on the chains and sprockets is obtained,and it concludes that the total tension of every chain is the sum of the static load and the corresponding proportion of dynamic load,and that imposing tension force can effectively reduce the vibration caused by the elongation of the chain wear.